2020
DOI: 10.1002/capr.12355
|View full text |Cite
|
Sign up to set email alerts
|

Survivor‐led relational psychotherapy and embodied trauma: A qualitative inquiry

Abstract: Background: Childhood sexual abuse has complex and multifarious consequences for one's physical and mental health, including injuries and psychological illnesses such as depression (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Trauma originating from the family has lasting effects. Other studies have also found that participants experienced rumination (Forde & Duvvury, 2020) and social isolation (Mert & Aksoy, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Trauma originating from the family has lasting effects. Other studies have also found that participants experienced rumination (Forde & Duvvury, 2020) and social isolation (Mert & Aksoy, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Massage appears to target physiological symptoms common after sexual violence and was found to help decrease chronic pain and body tension, lower biological markers of stress and anxiety, and decrease dissociation through increased body awareness and integration (Field et al, 1997; Jina & Thomas, 2013; Price, 2005). Qualitative research has also found support for incorporating the body into trauma treatment using a psychophysiological approach (Forde & Duvvury, 2021). In sum, research of treatment after sexual violence initially focused on investigating forms of psychotherapy and, resultingly, strong evidence existed for this treatment with this population.…”
Section: Introductionmentioning
confidence: 99%